Decoding China's Covid-19 "virus exceptionalism": Community-based digital contact tracing in Wuhan - Philipp Boeing; Yihan Wang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
During the COVID-19 pandemic, comprehensive, accurate, and timely digital contact tracing serves as a decisive measure in curbing viral transmission. Such a strategy integrates corporate innovation, government decision-making, citizen participation, and community coordination with big data analytics. This article explores how key stakeholders in an open innovation ecosystem interact within the digital context to overcome challenges to public health and socio-economic welfare imposed by the pandemic. To enhance the digital contact tracing effectiveness, communities are deployed to moderate the interactions between government, enterprises and citizens. As an example, we study the community-based digital contact tracing in Wuhan, a representative case of China's 'virus exceptionalism' in COVID-19 mitigation. We discuss the effectiveness of this strategy and raise critical ethical concerns regarding decision-making in R&D management.
Keywords: 330; COVID-19; digital contact tracing; open innovation ecosystem; community; big data